A remarkable new species of Sicophion Gauld, 1979 (Hymenoptera: Ichneumonidae) from Peru, with a key to the species - Alvarado, M. (Zootaxa, 2016)
The small Neotropical genus Sicophion currently comprises two described species. The genus is recorded for the first time in Peru and S. yana sp. n. is described. A key to species is also presented.